ENHANCING THE SANDY SOIL STRUCTURE OF THE SAMAS COASTAL AREA USING ANAEROBIC DIGESTION SLUDGE DERIVED FROM PALM OIL MILL EFFLUENT - Lisan, Ahmad Rif'an Khoirul; Amalia, Dwi; Dewanti, Tesa Oktafira; Pratama, Aldy Putra; Putra, Rizki Amanda; Yudhanto, Katon Dwi; Azzahra, Hilmaniya Shofia; Wardani, Nina Anggita (Jurnal Tanah dan Sumberdaya Lahan, 2025)
This study investigated the potential of anaerobic digestion sludge derived from palm oil mill effluent (POME) to enhance the structure of sandy soils in the Samas Coastal Area, Bantul Regency, Yogyakarta. Sandy soils, having low water retention and nutrient-holding capacity, present significant challenges for sustainable agriculture. By applying different volumes of digestate (0 ml, 50 ml, 100 ml, 200 ml, 400 ml, and 800 ml per kilogram of soil) in a 30-day greenhouse experiment, this research assessed the impact of POME sludge on soil structure improvements, particularly focusing on aggregation, porosity, and bulk density. Treatments with higher digestate volumes, especially 800 ml/kg, yielded substantial improvements in soil aggregation, contributing to better moisture retention. Enhanced aggregation facilitated improved water retention and root penetration, indicating that anaerobic digestion sludge could effectively amend sandy soil limitations. These findings underscore the potential of POME-derived organic amendments as sustainable soil conditioners, offering a dual benefit of waste valorization and enhanced agricultural productivity for marginal soils in coastal areas.